UJI TUBEX UNTUK DIAGNOSIS DEMAM TIFOID DI LABORATORIUM KLINIK NIKKI MEDIKA DENPASAR - Kusumaningrat, Ida Bagus Verry; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana)
Typhoid fever is one of the endemic diseases that commonly occur in rural and urban communities. It spreads through food and drink contaminated by Salmonella typhi bacteria. In 2008, detection of typhoid fever was carried out using the tubex test in which it principally detects the IgM antibody that specific for Salmonella typhi O9 present in serum by employing the method of Inhibition Magnetic Binding Immunoassay (IMBI).  The present study was aimed to evaluate results of blood sample examination of suspected typhoid fever patient using the tubex test, in order to confirm the typhoid fever diagnose. This research was retrospective study by analyzing 1.266 data of suspected patients obtained from Nikki Medika Clinic Laboratory. The samples were delivered to the Clinic Laboratory for laboratory examination since 2008 till October 2012. Each sample was examined using the tubex test. The results showed that 11.6 – 27.8% of the blood samples were positive for typhoid fever while 70 – 88.7% was negative.
Keywords: Salmonella typhi, Typhoid fever, Tubex test